Análise da potencialidade agrícola na região de predomínio do bioma miombo, ao norte de moçambique, com ênfase em características biofísicas do ambiente - Macarringue, Lucrencio Silvestre (2014)
Mozambique is in the process of agricultural expansion, particularly in the areas of predominance of Miombo Biome, mostly located in the northern part of the country, driven by the trilateral cooperation program (ProSAVANA) involving Mozambique, Brazil and Japan. Some studies were already conducted by this program, for instance, related to the adaptability of maize and soybean seeds in this area. This study aims to analyze, by the biophysical point of view, the favorability of the agricultural expansion in the northern part of Mozambique in the scope of ProSAVANA, based on the Japan- Brazil cooperation program (PRODECER) experiences in the western part of Bahia. As basic materials, digital elevation models from the Shuttle Radar Topography Mission (SRTM) were used to generate hypsometric and slope maps from both sites, Tropical Rainfall Measuring Mission (TRMM) to compare rainfall data from both sites, data from MODIS/Terra (MOD13Q1) sensor to compare the structure of the most representative biome from both regions. Spatial database containing watershed boundary, forest reserves and soils types were also considered. Techniques of digital image processing, spatial analysis and spatial modeling available in the ENVI 4.8TM and ArcMapTM 10 software packages were used. For the best performance of the EVI data, the Double Logistic filter available in the TIMESAT 3xTM software was applied. Data were analysed based on statistical methods of frequency, histogram and regression. As results, a map of suitability for agricultural expansion areas based on physiographic parameters were obtained over 4.8 million hectares (73 percent of the total area) as well as a database with information of the physical conditions of the both region. The method used here was relatively simple and can be reproduced for other similar researches.